Complete Genome Sequence of a Propionibacterium acnes Isolate from a Sarcoidosis Patient - Minegishi, Kana (American Society for Microbiology, 2013)
Propionibacterium acnes is a human skin commensal that resides preferentially within sebaceous follicles and is the only microorganism that has been isolated from sarcoid lesions. We report the complete genome sequence of P. acnes, which was isolated from a Japanese patient with sarcoidosis.